CHILEAN SOCIALIST ACTIVISM AND RESISTANCE BETWEEN 1973 AND 1975:A STORY OF SACRIFICE - Blasco Rovira, Anna; Sierpe, Vladimir (Revista de Historia Social y de las Mentalidades, 2024)
From 1973 until 1975 the first clandestine  leadership of the PSCH (Chilean Socialist  party) was active in Chile, mainly in the Capital  Santiago. Through the methodological tools of  Collective Behavior and Social Movements’  sociology, we aim to explain how and why a  group of young socialists was politically active  until their very end. In other words, how the  network structure, in a particularcontext, created  the conditions of the sacrifice of the network’s  actors.We plan to analyze historical context as  well as actors’ socialization processes. Based on  historical facts and events we will try to present  their political pathways which ended with their  disappearances and deaths. Methodologically,  we are presenting different types of sources and  data, mainly oral ones, which were gathered by  scholars from Chile and from other countries.  Doing so we can present here the conditions and  characteristics of one socialist group’s activism.  We deal chronologically with the various facts  and events in order to underline the political  dimension of their activities
Keywords: Socialism; Clandestinity; Activism; Repression